Efficacy of breast reconstruction for N2‐3M0 stage female breast cancer on breast cancer‐specific survival: A population‐based propensity score analysis - Yuting Zhao; Lutong Yan; Shouyu Li; Zejian Yang; Na Chai; Pei Qiu; Huimin Zhang; Jianjun He; Can Zhou (Cancer Medicine)
Abstract Background The efficacy of breast reconstruction for patients with N2‐3M0 stage female breast cancer (FBC) remained unclear due to the lack of randomized clinical trials. This retrospective study aimed to explore the efficacy of breast reconstruction for patients with N2‐3M0 stage FBC. Methods Two thousand five hundred forty‐five subjects with FBC staged by N2‐3M0 from 2010 to 2016 were retrieved from the Surveillance, Epidemiology, and End Results database. Generalized boosted model (GBM) and propensity score matching (PSM) analyses and multivariable Cox analyses were employed to assess the clinical prognostic effect of postmastectomy reconstruction for patients with N2‐3M0 stage FBC in breast cancer‐specific survival (BCSS). Results Totally, 1784 candidates underwent mastectomy alone (mastectomy group), and 761 candidates underwent postmastectomy reconstruction (PMbR group), with 418 breast‐specific deaths after a median follow‐up time of 57 months (ranging from 7 to 227 months). BCSS in the mastectomy group showed no statistical difference from that in the PMbR group in the PSM cohort (HR = 0.93, 95% CI: 0.70–1.25, p = 0.400) and GBM cohort (HR = 0.75, 95% CI: 0.56–1.01, p = 0.057). In the multivariate analyses, there was no difference in the effect of PMbR and mastectomy on BCSS in the original cohort (HR = 0.85, 95% CI: 0.66–1.09, p = 0.197), PSM cohort (HR = 0.86, 95% CI: 0.64–1.15, p = 0.310), and GBM cohort (HR = 0.84, 95% CI: 0.61–1.17, p = 0.298). Triple‐negative breast cancer (TNBC) was a detrimental factor affecting BCSS for patients in the PMbR group. Conclusions Our study demonstrated that PMbR is an oncologically safe surgical treatment and can be widely recommended in clinics for females with non‐TNBC staged by T0‐3N2‐3M0.